Converging disciplines a transdisciplinary research approach to urban health problems - Kirst, Maritt 1974-.; SpringerLink (Online service). (New York Springer, 2011)
Converging Disciplines: A Transdisciplinary Research Approach to Urban Health Problems Maritt Kirst, Nicole Schaefer-McDaniel, Stephen Hwang, and Patricia O?Campo Centre for Research on Inner City Health, Toronto, Canada As urban populations grow, new health problems evolve in tandem with longstanding issues. And as a welter of social, environmental, and access factors further complicate the picture, workable solutions require increasingly sophisticated understanding and innovative methods?generally beyond the scope of one professional field. Converging Disciplines introduces the concept of transdisciplinary research as a multidimensional, research-to-practice approach to urban health issues, not only bringing researchers together but also linking stakeholders, from practitioners to policymakers to community members. This immediately accessible volume differentiates transdisciplinary research from multi- and interdisciplinary strategies, as well as from popular community-based models, and brings a uniquely North American set of perspectives to the concept. Chapter authors explore the theory behind the methods as well as their application in meeting chronic problems (e.g., domestic violence, substance abuse) and working with vulnerable populations (e.g., homeless individuals, refugees) in ways that are ecologically based, ethically sound, and eminently practical. Key areas of coverage: Benefits and challenges of transdisciplinary research in the urban health setting. Transdisciplinary research process, including methodologies, collaboration, and information sharing. Detailed case examples of transdisciplinary research used in addressing health issues among marginalized urban populations. An overview of training programs in the U.S. and Canada. The view from funding agencies. Preparing the university, researchers, and the job market for a transdisciplinary future. Researchers and graduate students in urban and public health will find inspiring reading in Converging Disciplines: a bold framework for transforming their fields, and the tools for meeting the new generation of urban health challenges.
Introducing a transdisciplinary approach to applied urban health research -- Benefits and challenges of transdisciplinary research for urban health researchers -- In search of empowering health research for marginalized populations in urban settings: the value of a transdisciplinary approach -- Reducing health disparities experienced by refugees resettled in urban areas: a community-based transdisciplinary intervention model -- The Street Health Report 2007: community-based research for social change -- Safety as a social value: revisiting a participatory case study in Scotland -- Methodological notes on conducting transdisciplinary research -- Collaborative processes in transdisciplinary research -- From complex problems to complex problem-solving: transdisciplinary practice as knowledge translation -- Transdisciplinary training in health research: distinctive features and future directions -- Funding agencies and transdisciplinary research -- Moving forward: the future of transdisciplinary health research.
Electronic reproduction.
Keywords: Urban health; Community-based participatory research -- Methods; Public health; Qualitative research; Social problems; Socioeconomic factors; Electronic books